Java SE 8 for the really impatient - Horstmann, Cay S., 1959- (Addison-Wesley, 2014)
Eagerly anticipated by millions of programmers, Java SE 8 is the most important Java update in many years. The addition of lambda expressions (closures) and streams represents the biggest change to Java programming since the introduction of generics and annotations. Now, with Java SE 8 for the Really Impatient, internationally renowned Java author Cay S. Horstmann concisely introduces Java 8's most valuable new features (plus a few Java 7 innovations that haven't gotten the attention they deserve). If you're an experienced Java programmer, Horstmann's practical insights and sample code will help you quickly take advantage of these and other Java language and platform improvements. This indispensable guide includes Coverage of using lambda expressions (closures) to write computation "snippets" that can be passed to utility functions The brand-new streams API that makes Java collections far more flexible and efficient Major updates to concurrent programming that make use of lambda expressions (filter/map/reduce) and that provide dramatic performance improvements for shared counters and hash tables A full chapter with advice on how you can put lambda expressions to work in your own programs Coverage of the long-awaited introduction of a well-designed date/time/calendar library (JSR 310) A concise introduction to JavaFX, which is positioned to replace Swing GUIs, and to the Nashorn Javascript engine A thorough discussion of many small library changes that make Java programming more productive and enjoyable This is the first title to cover all of these highly anticipated improvements and is invaluable for anyone who wants to write tomorrow's most robust, efficient, and secure Java code.